Protective effect of nanosilica on irradiated dates against saw toothed grain beetle, Oryzaephilus surinamensis (Coleoptera: Silvanidae) adults. (May 2021) - Zahran, N.F.; Sayed, R.M.
Abstract: The insecticidal activity of nanosilica particles (NSPs) [20 ± 4 nm] was determined using the saw-toothed grain beetle, Oryzaephilus surinamensis (L) adults as the experimental insect. When the unsexed adults were exposed to different doses of nanosilica (0.2, 0.4, 0.6, 0.8 and 1.0 mg/Petri dish) for different periods (1, 2 and 3 days), it was found that NSPs had more insecticidal activity against O . surinamensis . Moreover, it was found that as the exposure time and dose increased, the mortality percentages of the adults increased. When the adult fed on irradiated dates which treated with different doses of nanosilica (0.5, 1, 2 and 4 mg/ 1date) the mortality was higher than in nanosilica alone. The LD50 of the bioassay tests showed that the calculated LD50 values of each treatment were 0.468, 1.201 and 0.572 mg/1date. The adult of O. surinamensis (untreated, treated with LD50 of nanosilica and fed on unirradiated or irradiated dates) examined by a scanning electron microscope. The examination showed the same malformations in all treatments which caused abrasion and damage on the outer surface. Nanosilica can be effectively replacing chemical insecticides to protect stored products. Highlights: Oryzaephilus surinamensis is one of the most destructive date pests. Nanosilica combined with gamma radiation was tested in lab trials as new safe control tool to reduce using chemical insecticides. Nanosilica and gamma radiation significantly improved control of Oryzaephilus surinamensis in stored dates.